Stiftung für Kunst und Kultur. - Stiftung für Kunst und Kultur, Bonn; Smerling, Walter (Bonn : Stiftung für Kunst und Kultur e.V., 1997)
Baselitz, Georg ; Behkalam, Akbar ; Beuys, Joseph ; Darboven, Hanne ; Fritsch, Lutz ; Graubner, Gotthard ; Jin, Guo ; Lüpertz, Markus ; Maffini, Eugenio ; Mattheuer, Wolfgang ; Nanoo, Samir ; Peichl, Gustav ; Richter, Gerhard ; Rübsaamen, Dieter ; Swan, Douglas ; Weidl, Peter ; Yue Minjun
Duits
boek